The feasibility study of CaCO3 derived from cockleshell as nanoparticle in chemically modified lubricant - Zainal, Nurul Adzlin; Mohd Zulkifli, Nurin Wahidah; Yusof, Mahshuri; Hassan, Masjuki; Yunus, Robiah (Malaysian Tribology Society, 2015)
Calcium carbonate (CaCO3) is one of the most abundant minerals in nature. CaCO3 nanoparticles were synthesized from cockle shells. The tribological properties of the CaCO3 nanoparticles as an additive in bio-based lubricant were evaluated with a four-ball tester. The bio-based lubricant is a mixture of PAO and 5% palm oil-based TMP ester. The results show that these CaCO3 nanoparticles improved the tribological properties of bio-based lubricant. The optimum concentration of CaCO3 nanoparticles is 8 wt.%. The results show that a boundary film mainly composed of CaCO3, CaO, and iron oxide was formed on the worn surface during the friction process to protect the surface.